Research on autonomous walking performance and electromechanical characteristics of mining double-track chassis. - Zeren Chen; Yongpeng Wang; Fei Yang; Ruibin Li; Peng Han; Duomei Xue (PLoS ONE)
To study the autonomous walking performance and corresponding electromechanical characteristics of unmanned mining equipment under different slopes, turning radii, and ground conditions. Firstly, the autonomous walking systems based on PID, fuzzy PID, and BP PID, in this paper, are constructed, and then the electromechanical coupling simulation is carried out to analyse autonomous walking performance and electromechanical characteristics of mining double-track chassis under different working conditions. Finally, the feasibility of the autonomous walking system based on fuzzy PID is verified by the path-tracking experiment. The results show that the autonomous walking performance of the autonomous walking system based on the fuzzy PID is the best. Under the soft ground, the current, voltage, and load torque are all increased to varying degrees due to the sinking phenomenon of the crawler, but the driving speed is reduced, and when mining double-track chassis makes large-radius turns, the autonomous walking system based on the BP PID can also be given priority with a path deviation within 0.1 m.